Dandelion (Taraxacum officinale L.) root components exhibit anti-oxidative and antiplatelet action in an in vitro study. (August 2019) - Lis, Bernadetta; Rolnik, Agata; Jedrejek, Dariusz; Soluch, Agata; Stochmal, Anna; Olas, Beata
Graphical abstract: Highlights: Dandelion root fractions are typified by anti-adhesive and anti-aggregation action. Phenylacetate inositol esters fraction (C) showed the strongest antiplatelet action. Hydroxycinnamic acids fractions (D and E) showed the strongest anticoagulant effect. Fractions A (amino-acid-sesquiterpene lactones) and C showed the highest anti-oxidative action. Abstract: The effect of dandelion root and its various ingredients on the biological functions of blood platelets has not been well investigated. Thus, the objective of our in vitro study was to examine the five root fractions (A–E), differing in chemical composition, for changes induced in the human platelets' model using selected hemostatic parameters. As a result, the best anti-platelet potential was shown by preparation enriched with hydroxyphenylacaetate inositol esters – PIEs (fraction C). On the other hand, the best overall protective effect against oxidation of lipids and proteins of platelets, and the best inhibitory effect on the generation of O2 − were observed in the presence of fraction A (SL-amino acid adducts enriched fraction). Thus, PIEs and SLs rich plant organs, such as dandelion root, may be considered as potentially suitable additives for functional food products used in prophylaxis and treatment of cardiovascular diseases associated with hyperactivation of blood platelets.